Respostas
respondido por:
3
Boa tarde
3x + 2y = 0
5x + 3y = - 1
isolamos x na primeira equação
3x = - 2y ---> x = - 2y / 3
substitui na segunda equação
5(- 2y / 3) + 3y = - 1
- 10y / 3 + 3y = - 1
mmc = 3
- 10y + 9y = - 3
- y = - 3 (-1)
y = 3
acha x agora
3x = - 2y
3x = - 2.3
x = - 6 / 3
x = - 2
S = {- 2, 3}
3x + 2y = 0
5x + 3y = - 1
isolamos x na primeira equação
3x = - 2y ---> x = - 2y / 3
substitui na segunda equação
5(- 2y / 3) + 3y = - 1
- 10y / 3 + 3y = - 1
mmc = 3
- 10y + 9y = - 3
- y = - 3 (-1)
y = 3
acha x agora
3x = - 2y
3x = - 2.3
x = - 6 / 3
x = - 2
S = {- 2, 3}
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás